Global Trends in Measuring the Innovative Potential of an Enterprise - K. A. Sarsen; K. A. Кirdasinova; A. A. Orozonova (Экономика: стратегия и практика, 2023)
The purpose of the study: qualitative and quantitative comparison of tools for assessing the effectiveness of the use of the innovative potential of the enterprise. To achieve the research goal, the following tasks are set: to study the structure of the components of innovation potential in the context of achieving business efficiency; evaluate the tools used in practice to study the innovative potential of the enterprise; compare the tools for assessing the innovative potential of enterprises in terms of profitability and efficiency of the enterprise. The results of this study will allow us to substantiate the modern concept of innovative activity of the enterprise, based on the structure of innovative potential, consisting of four components: research, personnel, material and technical base, and corporate entrepreneurship. Secondly, the study aims to assess the enterprise’s innovative potential, which differs in the quality and quantity of indicators used. The measurement tools used in practice include a balanced scorecard; multilevel assessment using a tree of cluster factors; assessment based on world indices and/or monitoring; mixed and statistical approach. Thirdly, it was found that on the basis of practical and value criteria, a system of balanced indicators of the innovative potential of an enterprise and an economic justification for the development of developed economic structures, as well as for enterprises focused on innovative capitalization and corporate entrepreneurship, is effective. Tools with probabilistic, analytical and statistical measurement methods are also useful for developed sectors of the economy and for enterprises focused on sustainable business.